Postoperative acute kidney injury after on-pump cardiac surgery in patients with connective tissue disease - Zhang, Xue; Miao, Qi; Yu, Chunhua; Zhang, Yuelun; Wu, Di; Tian, Yajie; Li, Hanchen; Wang, Chunrong (Frontiers in Cardiovascular Medicine, 2023)
Objective: Patients with connective tissue disease have a poor prognosis after receiving cardiac surgery. This study described the clinical scenarios and investigated factors correlated with acute kidney injury (AKI) after on-pump cardiac surgery in patients with systemic lupus erythematosus (SLE) or vasculitis. Methods: Patients with SLE or vasculitis who underwent on-pump cardiac surgery from March 2002 to March 2022 were enrolled, while patients with preoperative renal dysfunction were excluded. AKI was defined according to the Kidney Disease: Improving Global Outcomes (KDIGO) criteria. Uni- and multivariable analyses were performed to identify potential factors associated with postoperative AKI. Results: Among 123 patients enrolled, 39 (31.7%) developed AKI within seven days after receiving on-pump cardiac surgery. Four patients died in the hospital, resulting in an overall in-hospital mortality of 3.3%, and all deaths occurred in the AKI group. Patients in the AKI group also had longer ICU stays (median difference 3.0 day, 95% CI 1.0 to 4.0, P<0.001) and extubation time (median difference 1.0 days, 95% CI 0 to 2.0, P<0.001) than those in the non-AKI group. Multivariable logistic regression revealed that BMI over 24 kg/m2 (OR 3.00, 95% CI 1.24 to 7.28) and comorbid SLE (OR 4.73, 95% CI 1.73 to 12.93) were independently correlated with postoperative AKI. Conclusion: Factors potentially correlated with AKI following on-pump cardiac surgery in patients with connective tissue disease were explored. Clinicians should pay more attention to preoperative evaluation and intraoperative management in patients with risk factors.